A qualitative exploration of participants' experiences of taking part in a walking programme: Perceived benefits, barriers, choices and use of intervention resources. (22nd December 2016) - Mitchell, Fiona; Stalker, Kirsten; Matthews, Lynsay; Mutrie, Nanette; Melling, Chris; McConnachie, Alex; Murray, Heather; Melville, Craig A.
Abstract : Background: Adults with intellectual disabilities (ID) experience significant inequalities and tend to be more sedentary and less physically active than the wider population. Walking programmes are an effective way to increase physical activity (PA) but have not been used in studies involving adults with intellectual disabilities. Method: Nineteen adults with intellectual disabilities participated in semistructured interviews or focus groups exploring their experiences of taking part in a walking programme (Walk Well). Data were coded using thematic analysis. Results: Four overarching themes emerged: perceived benefits of taking part in the programme, perceived drawbacks/ barriers, walking choices and using the Walk Well resources. While there was not a significant increase in walking for all, the participants reported positive experiences of taking part in the programme. Self‐monitoring proved difficult for some, particularly reading the daily step count recorded on the pedometer and writing it in the diary. Carers also played an important role in facilitating and preventing behaviour change in adults with intellectual disabilities. Conclusion: Additional barriers prevent many adults with intellectual disabilities from participating in PA. Capturing participant experiences provides important information for designing effective and equitable health improvement programmes.